Management of business processes of a commercial enterprise in the conditions of digitalization - K.O. Buzhymska; I.M. Tsaruk (Економіка, управління та адміністрування)
The article examines the current issues of the development of the business process management system of a trading enterprise in the conditions of digitalization. It is proposed to consider the business process management system of a trading enterprise in the conditions of digitalization as an integrated set of technological solutions and methods aimed at automation, optimization and control of all stages of the trading companyʼs activity. It has been established that this system allows a trading company to effectively coordinate its internal operations, such as inventory management, logistics, sales and interaction with customers and suppliers. On the basis of the presented scientific generalization, the value of digitalization in the business process management system of trade enterprises was characterized and it was determined that the introduction of digital technologies allows automating routine processes, reducing costs and speeding up the execution of tasks. Through data analysis, companies can better understand customer needs, optimize product assortments, and improve marketing strategies. The process of digitalization in the business process management system of trade enterprises was studied, which can be formed according to the following stages: analysis of current business processes; definition of digital needs and goals; selection and implementation of digital technologies; integration of new systems; staff training; testing and optimization; monitoring and continuous improvement. It is justified that since each business process has its own specific characteristics and requirements, the choice of digital solutions should be accurate and meet the specific goals of the company. It has been proven that various means of digitization can be applied to individual business processes of a trading enterprise, increasing their efficiency and competitiveness. At the same time, only a comprehensive approach to the development of business process management systems in the context of digitalization is crucial for ensuring efficiency and flexibility in the retail trade sector. A generalization of possible and expedient means of digitalization of individual business processes of a trade enterprise is presented (developed by the author). It is well-founded that the systematic implementation of digital solutions contributes to the sustainable development of the company and its adaptation to changing market conditions.